Policy Considerations on the Interplay Between State Aid Control and Competition Law - Maria João Melícias (Market and Competition Law Review)
Under the broad topic of the interplay between state aid and competition law, this article addresses the following related lines of discussion: (i) the goals and some of the political rationales of state aid control; (ii) a brief illustration of some of the harm caused by state aid, including a distinction between its anticompetitive and distortive effects; (iii) a description of the Portuguese legal and institutional framework on domestic state aid, including the underlying rationale for this institutional design; (iv) an assessment of the policy concerns that a scenario whereby the AdC would hold full-fledged enforcement powers against state aid might raise, and, finally (v) the competition advocacy role played by the AdC in relation to state-induced competition distortions, such as state aid or subsidies. The article concludes by putting into context the references included in recent EU policy statements on the importance of “fair competition” or “equitable markets” and recalls the need to avoid that similar standards contaminate antitrust enforcement or merger control, given the risks that “mixed” policy objectives in those domains might entail. It signals, in any event, the virtues of this new found rhetoric: the fact that it helps to engage the common citizen on the importance of competition. Such popular, less technocratic approach can be instrumental in bringing competition enforcement “down to earth”.